{2,6-Bis[1-(phenylimino)ethyl]pyridine-κ(3) N,N′,N′′}dichloridocobalt(II) - Li, Xiao-Gang (International Union of Crystallography, 2008)
In the title complex, [CoCl(2)(C(21)H(19)N(3))], the Co(II) atom is coordinated by one pyridine and two imine N atoms and by two chloride anions in a distorted trigonal bipyramidal geometry. The structure exhibits a pseudo-mirror plane through the metal atom, two chloride anions and the pyridine ring. In the crystal structure, the complexes are connected via intermolecular C—H⋯Cl hydrogen bonding.